2020
DOI: 10.1038/s41598-020-67104-4
|View full text |Cite
|
Sign up to set email alerts
|

Mucus layer modeling of human colonoids during infection with enteroaggragative E. coli

Abstract: EAEC is a common cause of diarrheal illness worldwide. Pathogenesis is believed to occur in the ileum and colon, where the bacteria adhere and form a robust aggregating biofilm. Among the multiple virulence factors produced by EAEC, the Pic serine protease has been implicated in bacterial colonization by virtue of its mucinolytic activity. Hence, a potential role of Pic in mucus barrier disruption during EAEC infection has been long postulated. In this study, we used human colonoids comprising goblet cells and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 64 publications
4
33
0
Order By: Relevance
“…Robust infection of the appropriate site of GI tract was observed with each pathovar, with comparable rates of adherence and minimal recoveries upon gentamicin to indicate a lack of invasion. The infection patterns and microscopic evaluations are in agreement with previous and recent analyses of organoid monolayer-based systems (11, 56, 57, 72), as well as with established literature regarding actin association and pedestal formation, or aggregative adherence patterns (37, 38). As with Shigella and Salmonella analyses, the future applications of the HIODEM model system with all E. coli pathotypes are broad and expected to provide key insights into human-specific pathology, including infection analyses in other segments of the GI tract for each pathovar.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Robust infection of the appropriate site of GI tract was observed with each pathovar, with comparable rates of adherence and minimal recoveries upon gentamicin to indicate a lack of invasion. The infection patterns and microscopic evaluations are in agreement with previous and recent analyses of organoid monolayer-based systems (11, 56, 57, 72), as well as with established literature regarding actin association and pedestal formation, or aggregative adherence patterns (37, 38). As with Shigella and Salmonella analyses, the future applications of the HIODEM model system with all E. coli pathotypes are broad and expected to provide key insights into human-specific pathology, including infection analyses in other segments of the GI tract for each pathovar.…”
Section: Discussionsupporting
confidence: 90%
“…Organoid-derived epithelial monolayer models like the HIODEM have enabled infection analyses by providing a process by which pathogens can directly interact with the apical side of the epithelium (11,24,33,(54)(55)(56)(57)(58). While three-dimensional organoid systems are available (40,(59)(60)(61)(62)(63) and "apical-out" organoid systems have been developed 64 ileum, cecum, or colon, despite the overall pluripotent state of the stem cells (11,15,71).…”
Section: Discussionmentioning
confidence: 99%
“…Growing colonoids in 2D monolayers may alleviate some of the limitations of 3D culture systems, and protocols detailing the methods to grow colonoids in 2D monolayers have been published recently. 46,47 In C57BL/6J mice colonized with ETBF, we showed a significant increase in glucosylceramide levels in the distal colon. In general, sphingolipid levels in the distal colon were higher than that of the proximal colon (data not shown).…”
Section: Discussionmentioning
confidence: 78%
“…Experiments that could be performed on colonoids within the Matrigel (colonoid bursting events and colonoid morphology changes) or in colonoids immediately lysed after removal from the Matrigel (lipid and protein collection) were inherently less prone to alterations caused by handling. Growing colonoids in 2D monolayers may alleviate some of the limitations of 3D culture systems, and protocols detailing the methods to grow colonoids in 2D monolayers have been published recently 46,47 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the mucus is also the first barrier protecting the gut from being invaded by the bacteria. Mucus is critical for the intestinal health since disruption of this boundary will probably result in bacterial penetration of mucus barrier and induce intestinal inflammation (Liu et al, 2020;Sharma et al, 2020;Son et al, 2020). It has been reported that gut bacteria could colonize the intestinal mucus layer in vivo and adhere to HT-29 cell in vitro (Altamimi et al, 2016;Engevik et al, 2019).…”
Section: Introductionmentioning
confidence: 99%